THE IMPACTS OF THE USE OF EDUCATIONAL TECHNOLOGY IN LEARNING ENGLISH IN THE POST PANDEMIC ERA: A CASE AT STKIP PARACENDEKIA NW SUMBAWA - Warda Martia; solihin (GLOBAL: Education Language and Humanity Journal, 2024)
Around the beginning of 2022, the Indonesian government implemented the new normal era as the sign of the end of Covid-19 gradually. However, the activities of the Indonesian people as a whole did not return to normal as usual. For example, in the education sector, especially in STKIP Paracendekia NW Sumbawa, it continued to apply Blended Learning System (BLS) in the learning process at the institution. Therefore, it was needed to conduct a research to know the impact of using educational technology in the post-pandemic learning process at STKIP Paracendekia NW Sumbawa as a basis for consideration in policy making at the institution. The purposes of the study were: 1) To identify what kind of educational technology is used to learn English in the post pandemic era; 2) To find out how those educational technologies are applied; and 3) To reveal the impacts of using educational technologies for learning English in the post-pandemic era. This research was conducted by using qualitative method. By this method, the purposive-sampling technique was used to determine the research subjects (4 participants). The techniques of data collection used triangulation-technique (observation, interview, and documentation) which were analyzed by reduction, display, and conclusion drawing and verification. Based on the results of the data analysis, there were various educational technologies (are LMS or Moodle, Zoom, Whatsapp, KAHOOT, and Quizess) that were applied at STKIP Paracendekia NW Sumbawa which were applied by combining them comprehensively instead of partially. The impact of educational technologies for lecturer generally has more positive sigificances than the negative ones. Meanwhile, for students, the educational technologies have various impacts which depend on the student’s ability and the situation